Do Foreign Companies Conduct R&D in Developing Countries? - Alice H. Amsden; Ted Tschang; Akira Goto (Asian Development Bank Institute (ADBI), 2001)
Multinational companies tend to conduct little research and development (R&D) outside their homebase, especially in developing countries. Singapore represents an anomaly because its multinationalfirms are reputed to undertake locally not only R&D but applied and possibly even basic research.Nevertheless, short of hearsay or peering over the shoulder of a researcher, there is no systematic orobjective way to determine from outside whether or not the classification of any given R&D effort iscorrect.This paper tries to create a system for determining the content level of R&D. Giventraditional R&D types (pure science, basic research, applied research, exploratory development oradvanced development), it introduces a new comprehensive taxonomy of R&D characteristics, suchthat variations in a characteristic behave systematically according to R&D type. The characteristicswe explore are: the search and objective of an R&D investment; its intended output; its time frame; themeasures of performance to which it is subject; the techniques employed by its researchers; their skillsand qualifications; and the overall size of an R&D investment. The empirical determination of thesecharacteristics does not require any infringement of a laboratory's intellectual property.
hdl:11540/4119
Keywords: 330